Encapsulated pepper blend in the diet of confined Holstein bullocks: effect on ruminal volatile fatty acid profiles, growth performance, and animal health - Giacomelli C.M.* (2023)
© 2023, The Author(s), under exclusive licence to Springer Nature B.V.Dairy bulls in feedlots have been a viable alternative for dairy producers to reinforce the family’s income. Aspects such as balanced diets and proper management are essential for these animals to develop and allow an economic return fully. Plant extracts are performance enhancers and ruminal and intestinal health promoters. Therefore, this study aims to evaluate whether the addition of encapsulated pepper (EP) blend (Capsicum annuum, Capsicum frutescens, and Capsicum chinense — rich in capsaicin) interferes with the volatile fatty acid profile in the rumen and enhances the growth performance of Holstein bullocks in a feedlot. For the experiment, 24 whole bullocks were used, distributed into three treatments, with eight replicates per treatment (one animal as an experimental unit, kept in an individual stall): groups T0, T200, and T400, receiving 0 mg, 200 mg, and 400 mg EP/kg of concentrate, respectively. Knowing the intake of concentrate and the average body weight during the experiment, we calculated the dose in mg/kg/day of the EP; that is, the T200 animals consumed 2.45 mg EP/kg (body weight –BW)/day; and T400 consumed 4.9 mg EP/kg BW/day. The animals from T400 presented a more significant weight gain between days 15 and 45 of confinement compared to T0 (P=0.05). This same treatment (T400) had a trend of lower weight gain between days 46 and 90 (P=0.09). Likewise, the T400 group had higher feed efficiency than T0 between days 15 and 45. Furthermore, the treatments affected the white blood cell count, with the T400 bullocks showing a higher number of neutrophils and lymphocytes. Higher levels of C-reactive protein (CRP) were measured in the serum of steers from both groups that consumed pepper (P<0.01). Interaction between treatment × day was observed for the activity of glutathione enzymes (GST and GPx) and levels of lipoperoxidation (LPO) (characterized by antioxidant stimulation) associated with the reduction in serum LPO; similar antioxidant enzymes behavior was observed in the liver. In the small intestine (jejunum), the activities of antioxidant enzymes (GST and GPx) were lower in the two groups of cattle that consumed EP, and LPO was lower. The treatments affected the concentration of acetic acid in the rumen fluid, presenting lower levels in T400 compared to T200 and similar T0 (P≤0.05). There was an interaction of day vs. treatment for propionic acid, presenting a higher concentration on day 45 at T400 than T0. These results, therefore, allow us to conclude that adding 400 mg of pepper extract can be an excellent additive for weight gain at the beginning of the experiment; however, over time, this dose of additive negatively affects weight gain. Both EP doses stimulated serum and tissue antioxidant responses, reducing lipoperoxidation. However, the 400 mg EP/kg concentrate suggests a pro-inflammatory response (leukocytosis and elevated CRP), s probably related to the high dose (i.e., between 1.7 and 2.4 g/animal/day).